Influence of Ambient Temperature on Nanosecond and Picosecond Laser-Induced Bulk Damage of Fused Silica - L. Yang; X. D. Yuan; H. X. Deng; X. Xiang; W. G. Zheng; S. B. He; Y. Jiang; H. B. Lv; L. Ye; H. J. Wang; X. T. Zu (Advances in Condensed Matter Physics)
The nanosecond (ns) and picosecond (ps) pulsed laser-induced damage behaviors of fused silica under cryogenic and room temperature have been investigated. The laser-induced damage threshold (LIDT) and damage probability are used to understand the damage behavior at different ambient temperatures. The results show that the LIDTs for both ns and ps slightly increased at cryogenic temperature compared to that at room temperature. Meanwhile, the damage probability has an inverse trend; that is, the damage probability at low temperature is smaller than that at room temperature. A theoretical model based on heated crystal lattice is well consistent with the experimental results.